2014
DOI: 10.1080/01904167.2014.963116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Boron Application in Chestnuts: Nut Yield and Quality

Abstract: A field trial was conducted between 2006 and 2009 in order to quantify the effect of boron (B) application on the yield and quality of chestnuts. The trial was established in an acid soil derived from siliceous schist and two levels of B were applied. Fruit abortion and nut yield per tree were measured, and nut quality parameters and chemical composition of the kernel were determined.Foliar B concentration was 8.6 mg kg -1 in the control trees and 48.4 mg kg -1 in fertilized chestnuts. Boron improved fruit set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
3
11
1
5
Order By: Relevance
“…Leaf B levels clearly explain the decreased growth of chestnut in the NPK-B treatment. There is a set of studies in this region showing B deficiency in the leaf and crop response to applied B, both in chestnut (Portela et al, 2011(Portela et al, , 2015a and in olive (Arrobas et al, 2010;Rodrigues et al, 2011). Leaf Zn and Mn were significantly lower in LNPKB in comparison with NPKB treatments on some sampling dates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf B levels clearly explain the decreased growth of chestnut in the NPK-B treatment. There is a set of studies in this region showing B deficiency in the leaf and crop response to applied B, both in chestnut (Portela et al, 2011(Portela et al, , 2015a and in olive (Arrobas et al, 2010;Rodrigues et al, 2011). Leaf Zn and Mn were significantly lower in LNPKB in comparison with NPKB treatments on some sampling dates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in northern Portugal showed that chestnut may display symptoms of B deficiency (Portela and Louzada, 2012;Portela et al, 2015b) and responds to the application of the nutrient as a fertilizer (Portela et al, 2011(Portela et al, , 2015a, as do other important crops in the region, such as olive (Arrobas et al, 2010;Rodrigues et al, 2011). In the north of Portugal, symptoms of Mg deficiency also seem to occur with some frequency, at least in some lithological formations (Portela et al, 2003(Portela et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores constataram que a resposta mais ou menos acentuada ao B depende da ocorrência ou não de baixas temperaturas (Bell, 1997), facto este corroborado por Portela et al (2015). Com efeito, nos ensaios instalados em Jou (Murça) foi observada uma reacção do castanheiro mais notória em 2008, ano em que ocorreu uma vaga de frio anormal no período da floração.…”
Section: Factores Climáticos: Temperatura E Precipitaçãounclassified
“…A menor absorção do B induzida pela secura estival foi constatada por Jordão e Silva (1987) na oliveira, e por Portela et al (2015) no castanheiro. Neste último trabalho verificou-se que, no ano de 2009 (precipitação nula nos meses de agosto e setembro), a concentração de B no miolo da castanha foi reduzida a metade comparativamente a 2007 e 2008, tanto nas árvores adubadas como nas testemunhas.…”
Section: Factores Climáticos: Temperatura E Precipitaçãounclassified
See 1 more Smart Citation